2019
DOI: 10.1165/rcmb.2018-0110oc
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomics Analysis Identifies ACVR1B as a Candidate Causal Gene of Emphysema Distribution

Abstract: Genome-wide association studies (GWAS) have identified multiple associations with emphysema apicobasal distribution (EABD), but the biological functions of these variants are unknown. To characterize the functions of EABD-associated variants, we integrated GWAS results with 1) expression quantitative trait loci (eQTL) from the Genotype Tissue Expression (GTEx) project and subjects in the COPDGene (Genetic Epidemiology of COPD) study and 2) cell type epigenomic marks from the Roadmap Epigenomics project. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…With respect to the lung, TGF-β family proteins participate in normal lung development and are dysregulated in COPD, emphysema, asthma, and pulmonary fibrosis (Verhamme et al, 2015; Morris et al, 2003; Thomas et al, 2016). Genetic variants near TGF-β superfamily members TGFB2 (Castaldi et al, 2014; Cho et al, 2014), ACVR1B (Boueiz et al, 2019), LTBP4 (Wain et al, 2017), and BMP6 (Loth et al, 2014) have been identified in GWAS for lung function and COPD, but prior to this study the region near ACVR1B was the only one linked to a gene in the TGF-β pathway through functional studies (Boueiz et al, 2019). Our findings demonstrate that the emphysema-associated variant rs1690789 is located in an active gene regulatory region in human lung fibroblasts that interacts with the promoter region of TGFB2 and regulates TGFB2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the lung, TGF-β family proteins participate in normal lung development and are dysregulated in COPD, emphysema, asthma, and pulmonary fibrosis (Verhamme et al, 2015; Morris et al, 2003; Thomas et al, 2016). Genetic variants near TGF-β superfamily members TGFB2 (Castaldi et al, 2014; Cho et al, 2014), ACVR1B (Boueiz et al, 2019), LTBP4 (Wain et al, 2017), and BMP6 (Loth et al, 2014) have been identified in GWAS for lung function and COPD, but prior to this study the region near ACVR1B was the only one linked to a gene in the TGF-β pathway through functional studies (Boueiz et al, 2019). Our findings demonstrate that the emphysema-associated variant rs1690789 is located in an active gene regulatory region in human lung fibroblasts that interacts with the promoter region of TGFB2 and regulates TGFB2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Most common have been GWAS of lung function, the largest of which included over 400,000 subjects and identified 279 genetic loci [55]. GWAS have been performed for hyperinflation [56] and emphysema distribution [57,58], two phenotypes that are relevant for lung volume reduction therapies. Although exacerbations are an important outcome in clinical trials, no GWAS for COPD exacerbations have been published.…”
Section: Genome-wide Association Studies In Copd Pharmacogenomicsmentioning
confidence: 99%
“…Emphysema can be assessed based on quantitative analysis of chest CT scans [67]. GWAS have identified genome-wide significant associations with quantitative measures of emphysema [68,69], emphysema patterns [70], and emphysema distribution [57,58]. Some of the emphysema associations overlap with COPD GWAS findings, including genes such as HHIP and FAM13A, which have been demonstrated to influence emphysema in mouse smoking models [71,72].…”
Section: Genetics Of Copd Heterogeneity and Subtypesmentioning
confidence: 99%
“…As a result, expression quantitative trait locus (eQTL) studies that associate genetic variants to gene expression values have been used to identify functional gene targets of GWAS-identified loci. In COPD, this approach has identified putative causal variants affecting the expression of HHIP 2 , FAM13A 3 , TGFB2 4 , and ACVR1B 5 . However, eQTL studies do not capture all of the potentially relevant functional mechanisms through which causal variants may alter gene expression.…”
Section: Introductionmentioning
confidence: 99%